University students’ understanding and opinions of eating disorders: a qualitative study - Sheila Greenfield; Millie Manning (BMJ Open)
Background Eating disorders (EDs) affect 1.25 million people in the UK. Evidence suggests the public display stigma and poor mental health literacy (MHL) towards EDs. There is a high prevalence of EDs in university populations, so it is important to determine the MHL of this at-risk group. Qualitative research exploring the MHL of this population is incomplete.Objective Explore university students’ beliefs and opinions of EDs, their knowledge of symptoms, treatment and help sources and how these are influenced by biological sex.Design A qualitative study, using semistructured interviews analysed using inductive thematic analysis.Setting The University of Birmingham.Participants Seven female and seven male University of Birmingham students.Results Analysis revealed six themes, each with subthemes: ED characteristics, causes, body image, seeking help, stigma and awareness. Students displayed poor awareness towards ED signs and symptoms, causes and help sources. Students were not stigmatising towards EDs, but many perceived them as a female problem and believed society to be stigmatising. Many referenced informal sources of information such as social media and expressed a desire for ED teaching. Sex did not have a significant influence on knowledge or opinions of EDs in this study; however, there were some differences, for example, some males were more likely to see EDs as a weakness and to perceive themselves as having low levels of knowledge.Conclusions University students show broad awareness of EDs; however, knowledge of certain aspects of ED-MHL including help sources and symptom recognition was lacking. Although students were not stigmatising of EDs themselves, many perceived high levels of public stigma. This, alongside poor knowledge, may delay help-seeking. Campaigns educating students and the public about EDs would aid earlier diagnosis, improving long-term outcomes. Further research into awareness and knowledge in other populations would be beneficial.